Pengembangan Bimbingan Belajar Berdasarkan Profil Motivasi Belajar Santri Madrasah Tsanawiyah - Iqbal Muhammad Fauzan; Mamat Supriatna; Nadia Aulia Nadhirah (Universitas Muhammadiyah Mataram, 2025)
Abstract: Understanding students' learning motivation is essential for designing effective and targeted academic guidance services in Madrasah Tsanawiyah settings. This study aims to develop academic guidance services based on the learning motivation profiles of Madrasah Tsanawiyah students. A descriptive quantitative approach was employed, involving 58 students as participants. The motivation instrument was constructed based on affective, cognitive, and psychomotor aspects. The collected data were analyzed using descriptive statistical techniques to determine the levels of students' learning motivation. The results showed that the majority of students had moderate levels of motivation, predominantly driven by external factors. The guidance services were designed to enhance social interaction, self-confidence, perseverance, and active engagement in learning. These findings underscore the importance of academic guidance services tailored to the real needs of students as a holistic and effective approach to optimizing learning motivation. The services are not only relevant in the pesantren (Islamic boarding school) context but can also be adapted to other educational settings that require systematic interventions to strengthen learning enthusiasm and character development. The implications of this study support the implementation of sustainable services as a strategy for improving educational quality and student well-being.Abstrak: Pemahaman terhadap motivasi belajar santri penting dalam merancang layanan bimbingan belajar yang efektif dan tepat sasaran di lingkungan Madrasah Tsanawiyah. Penelitian ini bertujuan mengembangkan layanan bimbingan belajar berdasarkan profil motivasi belajar santri Madrasah Tsanawiyah. Pendekatan kuantitatif deskriptif digunakan dengan melibatkan 58 santri sebagai partisipan. Data yang terkumpul dianalisis menggunakan teknik statistik deskriptif untuk menentukan tingkat motivasi belajar santri. Instrumen motivasi disusun berdasarkan aspek afektif, kognitif, dan psikomotorik. Hasil menunjukkan mayoritas santri berada pada kategori motivasi sedang, dengan dominasi faktor eksternal. Layanan bimbingan dirancang untuk meningkatkan interaksi sosial, kepercayaan diri, ketekunan, dan keterlibatan aktif dalam pembelajaran. Temuan ini menegaskan pentingnya layanan bimbingan belajar berbasis kebutuhan nyata santri sebagai pendekatan holistik yang efektif dalam mengoptimalkan motivasi belajar. Layanan tersebut tidak hanya relevan dalam konteks pesantren, tetapi juga dapat diadaptasi untuk konteks pendidikan lainnya yang memerlukan intervensi sistematis guna memperkuat semangat belajar dan pembentukan karakter. Implikasi penelitian ini mendukung implementasi layanan berkelanjutan sebagai strategi peningkatan mutu pembelajaran dan kesejahteraan peserta didik.